The Role of School Supervisors in Enhancing Pedagogical Competence of Junior High School Teachers in Sabang City Through Academic Supervision - Intan, Cut (Lembaga KITA, 2023)
This research aims to provide a comprehensive description of the role of school supervisors in enhancing the pedagogical competence of junior high school teachers in Sabang City in the year 2023. The study employs a school action research design conducted over two cycles, involving action planning, implementation, observation, and reflection phases. The research subjects comprise 12 teachers requiring improvement in their pedagogical competence, specifically from SMP Nilai 3 Sabang and SMP Nilai 5 Sabang. Five teachers are from SMP Negeri 3, while seven are from SMP Negeri 5. Data collection utilizes observation techniques, and data analysis employs qualitative descriptive analysis with percentage calculations. Findings from the first cycle indicate that eight teachers have achieved the research success indicators, while four have not. In the second cycle, eleven teachers have met the success indicators, with only one teacher yet to do so. The percentage of teachers meeting the success indicators increased from 66.7% in the first cycle to 91.7% in the second cycle. There is a 25% improvement in the percentage of pedagogical competence from the first to the second cycle. In conclusion, this study, conducted by a school supervisor, demonstrates a significant enhancement in the pedagogical competence of junior high school teachers in Sabang City through the implementation of academic supervision